Volanesorsen for treatment of familial chylomicronemia syndrome. (3rd August 2021) - Lazarte, Julieta; Hegele, Robert A.
ABSTRACT: Introduction: Familial chylomicronemia syndrome (FCS) is a rare subtype of severe hypertriglyceridemia that affects 1 in 100, 000 to 1, 000, 000 individuals. The major risk to health is acute pancreatitis. FCS is defined by biallelic loss-of-function mutations in one of five canonical genes that encode proteins critical to lipolysis of large triglyceride-rich lipoprotein particles. Unlike the vast majority of patients with severe hypertriglyceridemia, FCS patients lack any lipolytic capacity and are thus resistant to standard medications. Areas covered: This review focuses on a mechanism that effectively reduces elevated triglyceride levels in FCS, namely interference of synthesis of apolipoprotein (apo) C-III. Volanesorsen is an antisense RNA drug administered subcutaneously that knocks down apo C-III, resulting in dramatic reductions in triglyceride levels both in FCS patients and in the wider population of subjects with severe hypertriglyceridemia. Expert opinion: Volanesorsen is a highly effective treatment to reduce elevated triglycerides in FCS patients, providing proof-of-concept of the validity of targeting apo C-III. However, off target effects of volanesorsen, including thrombocytopenia, may ultimately limit its use. Nonetheless, building on the knowledge derived from the volanesorsen experience, there is intensified interest in promising newer agents that also target apo C-III but have technical modifications that limit potential off target adverse effects.